Application of a low cost telemedicine link to the diagnosis of neonatal congenital heart defects by remote consultation. (1st August 1999) - Mulholland, H C; Casey, F; Brown, D; Corrigan, N; Quinn, M; McCord, B; Rogers, J; Craig, B G
Abstract : OBJECTIVE: To determine whether accurate remote echocardiographic diagnosis of congenital heart disease could be achieved using a low cost telemedicine system. DESIGN: Echocardiographic images obtained by a paediatrician from neonates suspected of having congenital heart disease were transmitted by a telemedicine link across two integrated service digital network (ISDN) lines to a regional paediatric cardiology unit for interpretation by a consultant paediatric cardiologist. The "tele-echo" diagnosis was verified by the paediatric cardiologist on direct consultation and echocardiography. SETTING: Neonatal unit of Altnagelvin Hospital, Londonderry (a district general hospital) and the regional paediatric cardiology department, Royal Belfast Hospital for Sick Children. MAIN OUTCOME MEASURES: Accuracy of the diagnosis made using the telemedicine link; impact on patient management. RESULTS: Between September 1995 and September 1997 echocardiographic images were transmitted on 63 patients. A diagnosis was made in 61 (97%) (transmitted images were unsatisfactory in two). Congenital heart disease was diagnosed in 42 patients. Fourteen patients with major congenital heart disease were accurately diagnosed within 24 hours of admission using the telemedicine link and were transferred to the regional paediatric cardiology unit. A further 28 with less serious congenital heart disease continued to be managed at the district general hospital. Congenital heart disease was excluded in 19. Follow up consultation confirmed accurate diagnosis or exclusion of congenital heart disease in 57 (93%). There were four inaccurate diagnoses (6.3%; three undetected small ventricular septal defects and one pulmonary stenosis). CONCLUSIONS: Transmitted images were of sufficient quality to allow confirmation or exclusion of major congenital heart disease. The telemedicine link facilitated early diagnosis and initiation of appropriate management in patients with complex congenital heart disease and avoided the need for transfer in those where significant congenital heart disease was excluded.